Hyperuricemia is associated with low cardiorespiratory fitness levels and excess weight in schoolchildren - Luiza N. Reis; Jane D.P. Renner; Cézane P. Reuter; Jorge A. Horta; Dulciane N. Paiva; Andréia R. de M. Valim; Ana P. Sehn; Elza D. de Mello; Miria S. Burgos (Elsevier, 2017)
Objective: To evaluate the possible association between hyperuricemia and cardiorespiratory fitness levels/nutritional profile, grouped into a single variable, in schoolchildren. Method: Cross-sectional study of 2335 students from Elementary schools, aged 7-17 years of both genders, stratified by conglomerates of a municipality in Southern Brazil. Body mass index (BMI) was calculated and cardiorespiratory fitness (CRF) was assessed by the 6-minute run/walk test. The BMI and CRF were grouped into a single variable, considering: (1) low and normal weight/fit; (2) low and normal weight/unfit; (3) overweight-obesity/fit; (4) overweight-obesity/unfit. The Poisson regression (prevalence ratio, PR) was used for the association between hyperuricemia and BMI/CRF ratio with 95% confidence intervals and differences were considered significant when p < 0.05. Results: There is an association, although subtle, between the presence of hyperuricemia with low levels of CRF and the presence of excess weight, when grouped into a single variable. Boys and girls with this condition have higher prevalence of hyperuricemia (PR: 1.07; p = 0.007 for boys; PR: 1.10; p < 0.001 for girls). Conclusion: Together, excess weight and low levels of cardiorespiratory fitness are associated with the presence of hyperuricemia in schoolchildren. Resumo: Objetivo: Avaliar a possível relação entre hiperuricemia com aptidão cardiorrespiratória e o estado nutricional, agrupados, em escolares. Método: Estudo transversal com 2335 escolares da educação básica de 7 a 17 anos, de ambos os sexos, estratificados por conglomerados de um munícipio do sul do Brasil. Foi calculado o índice de massa corporal (IMC) e a aptidão cardiorrespiratória (APCR) foi avaliada pelo teste de corrida/caminhada de 6 minutos. O IMC e a APCR foram agrupados em uma única variável, considerando: 1) baixo peso-normal/apto; 2) baixo peso-normal/inapto; 3) sobrepeso-obesidade/apto; 4) sobrepeso-obesidade/inapto. A regressão de Poisson (razão de prevalência; RP) foi utilizada para associação entre hiperuricemia e a relação APCR/IMC com intervalos de confiança de 95% e diferenças significativas consideradas para p < 0,05. Resultados: Observa-se associação, embora sutil, entre a presença de hiperuricemia com baixos níveis de APCR e a presença de excesso de peso, de forma agrupada. Meninos e meninas, com esta condição, têm maior prevalência de hiperuricemia (RP: 1,07; p = 0,007; RP: 1,10; p < 0,001, respectivamente), em comparação aos seus pares com bons níveis de APCR e estado nutricional adequado. Conclusão: De forma conjunta, o excesso de peso e os baixos níveis de aptidão cardiorrespiratória estão associados com a presença de hiperuricemia em escolares. Keywords: Hyperuricemia, Physical fitness, Overweight, Child, Adolescent, Palavras-chave: Hiperuricemia, Aptidão física, Excesso de peso, Criança, Adolescente